La hipertrofia a través del entrenamiento oclusivo, versus mediante el entrenamiento de fuerza - Coín, M.; Antonio, J. (Universidad Europea, 2022)
Blood occlusion has been widely investigated as a means of developing muscle mass in subjects with injuries or special conditions that prevent them from moving high loads. However, research related to its effects in high-performance athletes is still beginning, especially in judo. This creates an ideal situation for the proposal of a study that seeks to make a comparison between the effects of traditional strength-resistance training, and strength training under the effects of blood occlusion, focusing on the development of muscle mass, but without neglecting highly important aspects, such as the maximum values of force expression, and the resistance to said force. For this, a study has been developed that will look for the differences between traditional strength training and strength training in blood occlusion, in judokas. They will follow a 6-week protocol, in which each of the groups (control, traditional and occlusion), will work differently, enhancing the main characteristics of each methodology, to later make a comparison between the previous and subsequent situation, both between groups, as in the same.